Preserving plant samples from remote locations for detection of RNA and DNA viruses - Hamim, Islam; Suzuki, Jon Y.; Borth, Wayne B.; Melzer, Michael J.; Wall, Marisa M.; Hu, John S. (Frontiers in Microbiology, 2022)
Viral diseases in plants have a significant impact on agricultural productivity. Effective detection is needed to facilitate accurate diagnosis and characterization of virus infections essential for crop protection and disease management. For sensitive polymerase chain reaction (PCR)-based methods, it is important to preserve the integrity of nucleic acids in plant tissue samples. This is especially critical when samples are collected from isolated areas, regions distant from a laboratory, or in developing countries that lack appropriate facilities or equipment for diagnostic analyses. RNAlater® provides effective, reliable sample storage by stabilizing both RNA and DNA in plant tissue samples. Our work indicated that total RNA or DNA extracted from virus-infected leaf samples preserved in RNAlater® was suitable for reverse transcription polymerase chain reaction (RT-PCR), PCR, Sanger sequencing, high-throughput sequencing (HTS), and enzyme-linked immunosorbent assay (ELISA)-based diagnostic analyses. We demonstrated the effectiveness of this technology using leaf tissue samples from plants with virus symptoms grown in farmers' fields in Bangladesh. The results revealed that RNAlater® technology was effective for detection and characterization of viruses from samples collected from remote areas and stored for extended periods. Adoption of this technology by developing countries with limited laboratory facilities could greatly increase their capacity to detect and diagnose viral infections in crop plants using modern analytical techniques.